Inspiracje dla misyjnej działalności Kościoła w encyklikach Benedykta XVI - Adamiak, Grzegorz (Annales Missiologici Posnanienses, 2021)
The analysis carried out in the article indicates the truths about the Church contained in Benedict XVI’s encyclicals, which at the same time constitute specific inspirations for the missionary work of the Church ad gentes. The Pope does not distinguish between generally separate „missionary situations” and speaks rather of a single, fundamental, inalienable mission that still stands before the Church. Sometimes, however, he evokes the activity of the Church in mission areas. He reminds and points out that the Church’s ever-present task, including the mission ad gentes, is to remind and proclaim to the contemporary world the truth about God who is love. Missionary activity is also supposed to restore hope to modern man that goes beyond the temporal order. Finally, the Church’s mission, especially in the framework of her mission ad gentes, is to care for the true progress and development of every person and of the whole human society in truth and love. The missionary activity of the community Christ’s disciples remains a special area of such presence and witness of the Church in a world which is constantly globalizing.